2021
DOI: 10.1182/bloodadvances.2021004704
|View full text |Cite
|
Sign up to set email alerts
|

Decreased parasite burden and altered host response in children with sickle cell anemia and severe anemia with malaria

Abstract: Plasmodium falciparum malaria causes morbidity and mortality in African children with sickle cell anemia (SCA), but comparisons of host responses to P. falciparum between children with SCA (HbSS) and HbAA are limited. We assessed parasite biomass and plasma markers of inflammation and endothelial activation in children with HbAA (n=208) or HbSS (n=22) who presented with severe anemia and P. falciparum parasitemia to Mulago Hospital in Kampala, Uganda. Genotyping was performed at study completion. No child had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
(91 reference statements)
1
10
1
Order By: Relevance
“…One previous study involved children hospitalised with severe anaemia and malaria in Kampala, Uganda. The authors found that plasma PfHRP2 concentrations were significantly lower among 42 Although most of the children in our current study were recruited in areas where malaria transmission was considerably higher than in Kampala, overall concentrations of PfHRP2 were comparatively low, and were undetectable in almost a third of patients. We believe this finding was attributable to low-density infections rather than to pfhrp2 deletions 43 for several reasons.…”
Section: Discussioncontrasting
confidence: 51%
“…One previous study involved children hospitalised with severe anaemia and malaria in Kampala, Uganda. The authors found that plasma PfHRP2 concentrations were significantly lower among 42 Although most of the children in our current study were recruited in areas where malaria transmission was considerably higher than in Kampala, overall concentrations of PfHRP2 were comparatively low, and were undetectable in almost a third of patients. We believe this finding was attributable to low-density infections rather than to pfhrp2 deletions 43 for several reasons.…”
Section: Discussioncontrasting
confidence: 51%
“…The observed steady state hemoglobin concentration of 7.2-7.3 g/dL in children with SCD under five years of age was higher than the 6.3-6.9 g/dL reported elsewhere [9,14,22]; but lower than 8.1-9.3 g/dL, which was reported in the cooperative study involving patients with SCD conducted in Western countries [23]. These observations of differences in hemoglobin may be due to different factors, such as quality of care in children with SCD malaria infection, nutritional deficiency [24], and parasitic infections [25], which are more common in the least developed countries [26].…”
Section: Discussionmentioning
confidence: 61%
“…Malaria has played a profound role in the development of multiple genetic disorders affecting the red blood cells, but especially for the inherited haemoglobinopathies; the protective effects of sickle trait against severe malaria and death due to malaria are well established. Notably, SCA patients have lower levels of parasite burden than those with normal hemoglobin 16 17 . In this setting, why effective HU treatment of homozygous SCA individuals, did not increase but rather significantly reduced P. falciparum malaria in the REACH trial, is poorly understood.…”
Section: Discussionmentioning
confidence: 99%